2014
DOI: 10.1021/ie5014212
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Coarse Gibbsite Remaining in Hanford Nuclear Waste Tank Heels to Solid Sodium Aluminate [NaAl(OH)4·1.5H2O]

Abstract: This appendix contains Scanning Electron Microscopy Images of large gibbsite particles found in the heel of Hanford Tank 241-S-112. These images show the morphology and large size of the gibbsite typically found in Hanford waste heels. These samples are known to be gibbsite because Al and O where the only EDS observable elements of significant concentration in the particles and because gibbsite was the dominant Al-O-bearing phase observed by XRD in the samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…The most prevalent solids in the waste are gibbsite Al(OH) 3 and boehmite (γ-AlO(OH)), 6,7 but other salts and Ag, Ni, Pu, Pb, and Sr compounds are present. 8 Rheological responses are, in general, determined by the balance between repulsive and attractive particle interactions from colloidal, hydrodynamic, and frictional forces, influenced by the aforementioned physicochemical characteristics. 9,10 Unfortunately, the unique environments in the waste slurries impose limitations on the use of simple Deryaguin−Landau− Verwey−Overbeek (DLVO) theory 11 to describe the forces between particles, which are expected to be highly dependent on the structures of the crystal surfaces 12−14 and the surrounding solution.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most prevalent solids in the waste are gibbsite Al(OH) 3 and boehmite (γ-AlO(OH)), 6,7 but other salts and Ag, Ni, Pu, Pb, and Sr compounds are present. 8 Rheological responses are, in general, determined by the balance between repulsive and attractive particle interactions from colloidal, hydrodynamic, and frictional forces, influenced by the aforementioned physicochemical characteristics. 9,10 Unfortunately, the unique environments in the waste slurries impose limitations on the use of simple Deryaguin−Landau− Verwey−Overbeek (DLVO) theory 11 to describe the forces between particles, which are expected to be highly dependent on the structures of the crystal surfaces 12−14 and the surrounding solution.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A key challenge for understanding the rheological responses of these wastes is their complex physicochemical nature. They contain high concentrations of caustic dissolved salts (typically, pH > 11–12) and a wide variety of solid particles with broad size distributions (0.1–100 μm) and irregular shapes/rough surfaces. The most prevalent solids in the waste are gibbsite Al­(OH) 3 and boehmite (γ-AlO­(OH)), , but other salts and Ag, Ni, Pu, Pb, and Sr compounds are present . Rheological responses are, in general, determined by the balance between repulsive and attractive particle interactions from colloidal, hydrodynamic, and frictional forces, influenced by the aforementioned physicochemical characteristics. , Unfortunately, the unique environments in the waste slurries impose limitations on the use of simple Deryaguin–Landau–Verwey–Overbeek (DLVO) theory to describe the forces between particles, which are expected to be highly dependent on the structures of the crystal surfaces and the surrounding solution. , Examples of such complicated interactions include: (1) coupling between electrostatics and electrodynamics via the effect of ion fluctuation on van der Waals forces and dispersion contributions to electrostatic forces from ion–surface interactions and (2) restabilization of particles at high salt concentrations related to ion hydration.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is important to assess the composition of this component of the waste and the processing requirements to treat this waste. A number of aluminum phases have been identified in Hanford tank waste, including boehmite, [6][7][8] gibbsite, 9,10 sodium aluminate, 11,12 and alumino-silicates such as cancrinite. 13 Figure 2 provides sample Xray diffraction (XRD) patterns for boehmite and gibbsite rich phases in tank waste.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in addition to aspects of aluminum refining and corrosion sciences, this knowledge gap impacts the processing of radioactive high-level waste (HLW), currently stored in underground tanks at the U.S. Department of Energy sites such as the Hanford Nuclear Reservation, Washington. , These wastes are highly caustic, with hydroxide concentrations typically over 1 M and sodium concentrations reaching 11 M on average. , The waste is rich in Al 3+ , introduced as an ionic strength buffer during ion separations by codisposal and leaching of Al 3+ from fuel cladding and by addition of aluminum nitrate to reduce corrosion . Coexisting Al 3+ solids occur predominantly as the (oxy)­hydroxide mineral gibbsite [Al­(OH) 3 ] and boehmite (AlOOH). , Conversion of Al­(OH) 3 into hydrated, crystalline sodium aluminates in concentrated NaOH at ambient temperatures has been used to process HLW at Hanford, , and recent work has shown that transformation from monosodium aluminate hydrate to nonasodium bis­(hexahydroxy­aluminate) trihydroxide hexahydrate (NSA) proceeds spontaneously in the presence of excess sodium hydroxide monohydrate and water . This highlights that the ongoing physical and chemical manipulation of these complex waste slurries, such as their removal from tanks and safe disposal in glass waste forms, requires the development of robust models that reliably predict phase equilibria and transformation kinetics. …”
Section: Introductionmentioning
confidence: 99%
“…28 Coexisting Al 3+ solids occur predominantly as the (oxy)hydroxide mineral gibbsite [Al(OH) 3 ] and boehmite (AlOOH). 2,30−32 Conversion of Al(OH) 3 into hydrated, crystalline sodium aluminates in concentrated NaOH at ambient temperatures has been used to process HLW at Hanford, 33,34 and recent work has shown that transformation from monosodium aluminate hydrate to nonasodium bis-(hexahydroxyaluminate) trihydroxide hexahydrate (NSA) proceeds spontaneously in the presence of excess sodium hydroxide monohydrate and water. 35 This highlights that the ongoing physical and chemical manipulation of these complex waste slurries, such as their removal from tanks and safe disposal in glass waste forms, requires the development of robust models that reliably predict phase equilibria and transformation kinetics.…”
Section: Introductionmentioning
confidence: 99%